2021
DOI: 10.1002/ange.202102570
|View full text |Cite
|
Sign up to set email alerts
|

The Electrophilicity of Surface Carbon Species in the Redox Reactions of CuO‐CeO2 Catalysts

Abstract: Electronic metal–support interactions (EMSI) describe the electron flow between metal sites and a metal oxide support. It is generally used to follow the mechanism of redox reactions. In this study of CuO‐CeO2 redox, an additional flow of electrons from metallic Cu to surface carbon species is observed via a combination of operando X‐ray absorption spectroscopy, synchrotron X‐ray powder diffraction, near ambient pressure near edge X‐ray absorption fine structure spectroscopy, and diffuse reflectance infrared F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Considering that there is no relation between the CO conversions and specific surface areas, we can conclude that defects are only a minor factor in determining the catalytic activity; thus, a surface too rich in defects (e.g., rods) may not be beneficial for WGS over Cu/CeO 2 . This is further supported by the observation that the absolute change in absorption upon switching from argon to reaction conditions does not correlate with the WGS activity, consistent with previous results on CO oxidation, which have shown that the Ce 3+ fraction is not correlated with activity and that the state of copper is of greater importance …”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Considering that there is no relation between the CO conversions and specific surface areas, we can conclude that defects are only a minor factor in determining the catalytic activity; thus, a surface too rich in defects (e.g., rods) may not be beneficial for WGS over Cu/CeO 2 . This is further supported by the observation that the absolute change in absorption upon switching from argon to reaction conditions does not correlate with the WGS activity, consistent with previous results on CO oxidation, which have shown that the Ce 3+ fraction is not correlated with activity and that the state of copper is of greater importance …”
Section: Resultssupporting
confidence: 88%
“…Previous literature studies on Cu/CeO 2 catalysts have highlighted the importance of the copper oxidation state, ,,, which depends on both the gas-phase environment and the loading. ,, On the one hand, the interaction of metallic copper with oxygen vacancies (O vac ) was reported to enhance the reactivity, while on the other, copper was shown to have an oxidation state of +1 at the interface and to participate in the reaction, as supported by other studies, demonstrating the stability of oxidized copper under reductive conditions . In addition, a strong dependence of the state of copper on the gas phase at 180 °C was observed for 20 wt % Cu/CeO 2 , that is, mainly Cu 0 was detected during CO exposure and Cu + in the subsequent exposure to an inert gas . At low loadings, for example, 1 wt % Cu/CeO 2 , the catalyst behaves differently, as rather Cu + is observed under a CO atmosphere, which is then further oxidized to Cu 2+ on switching to He, indicative of electronic metal–support interactions.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Production of organic compounds, which is not based on fossil resources, should be developed to realize sustainable societies. In particular, C1 chemistry, utilizing one-carbon compounds (e.g., carbon dioxide, formic acid, formaldehyde, and methanol) as starting materials, has been of increasing importance [2][3][4][5][6][7] . Formaldehyde has the molecular formula, CH 2 O, and thus can be oligomerized to form sugars (monosaccharides) because the general molecular formula of sugars is (CH 2 O) n .…”
Section: Introductionmentioning
confidence: 99%